Peer-spectives: student employee and student user views of a library peer greeter service. Issue 2 (3rd April 2022) - Wood, Lana Mariko; Alexander, Stephanie; Carlos, Andrew
Abstract: The purpose of this study is to investigate the impact of implementing a peer greeter service point on increasing library use and decreasing library anxiety at a busy academic library. Researchers analyzed service point interaction data and conducted focus groups with both library student employees and students from the general student population in order to understand the impact of the peer greeter service point.